Systematic review of the long-term effects and economic consequences of treatments for obesity and implications for health improvement - Avenell, A; Broom, J; Brown, T; Poobalan, A; Aucott, L; Stearns, S; Smith, W; Jung, R; Campbell, M; Grant, A (Health technology assessment (Winchester, England), 2004)
To undertake a systematic review of the long-term effects of obesity treatments on body weight, risk factors for disease, and disease. The study encompassed three systematic reviews that examined different aspects of obesity treatments. (1) A systematic review of obesity treatments in adults where the methods of the Cochrane Collaboration were applied and randomised controlled trials (RCTs) with a follow-up of at least 1 year were evaluated. (2) A systematic epidemiological review, where studies were sought on long-term effects of weight loss on morbidity and/or mortality, and examined through epidemiological modelling. (3) A systematic economic review that sought reports with both costs and outcomes of treatment, including recent reports that assessed the cost-effectiveness of pharmaceutical and surgical interventions. A Markov model was also adopted to examine the cost-effectiveness of a low-fat diet and exercise intervention in adults with obesity and impaired glucose tolerance. The addition of the drugs orlistat or sibutramine was associated with weight loss and generally improved risk factors, apart from diastolic blood pressure for sibutramine. Metformin was associated with decreased mortality after 10 years in obese people with type 2 diabetes. Low-fat diets were associated with continuing weight loss for 3 years and improvements in risk factors, as well as prevention of type 2 diabetes and improved control of hypertension. Insufficient evidence was available to demonstrate the benefits of low calorie or very low calorie diets. The addition of an exercise or behaviour programme to diet was associated with improved weight loss and risk factors for at least 1 year. Studies combining low-fat diets, exercise and behaviour therapy suggested improved hypertension and cardiovascular disease. Family therapy was associated with improved weight loss for 2 years compared to individual therapy. There was insufficient evidence to conclude that individual therapy was more beneficial than group therapy. Weight lost more quickly (within 1 year), from the epidemiology review, may be more beneficial with respect to the risk of mortality. The effects of intentional weight loss need further investigation. Weight loss from surgical and non-surgical interventions for people suffering from obesity was associated with decreased risk of development of diabetes, and a reduction in low-density lipoprotein cholesterol, total cholesterol and blood pressure, in the long term. Targeting high-risk individuals with drugs or surgery was likely to result in a cost per additional life-year or quality-adjusted life-year (QALY) of no more than 13,000 British pounds. There was also suggestive evidence of cost saving from treatment of people with type 2 diabetes with metformin. Targeting surgery on people with severe obesity and impaired glucose tolerance was likely to be more cost-effective at 2329 British pounds per additional life-year. Economic modelling over 6 years for diet and exercise for people with impaired glucose tolerance was associated with a high initial cost per additional QALY, but by the sixth year the cost per QALY was 13,389 British pounds. Results did not include cost savings from diseases other than diabetes, and therefore may be conservative. The drugs orlistat and sibutramine appear beneficial for the treatment of adults with obesity, and metformin for obese patients with type 2 diabetes. Exercise and/or behaviour therapy appear to improve weight loss when added to diet. Low-fat diets with exercise, or with exercise and behaviour therapy are associated with the prevention of type 2 diabetes and hypertension. Long-term weight loss in epidemiological studies was associated with reduced risk of type 2 diabetes, and may be beneficial for cardiovascular disease. Low-fat diets and exercise interventions in individuals at risk of obesity-related illness are of comparable cost to drug treatments. Long-term pragmatic RCTs of obesity treatments in populations with obesity-related illness or at high risk of developing such illness are needed (to include an evaluation of risk factors, morbidity, quality of life and economic evaluations). Drug trials that include dietary advice, plus exercise and/or behaviour therapy are also needed. Research exploring effective types of exercise, diet or behaviour and also interventions to prevent obesity in adults is required.